Correlation between IgG Anti-Toxoplasmosis Gondii Antibodies and Cognitive Function in Human Immunodeficiency Virus-Acquired Immunodeficiency Syndrome (HIV-AIDS) Patients with Cerebral Toxoplasmosis - Puspitasari, Carina Shelia; Fitri, Fasihah Irfani; Ritarwan, Kiking (TALENTA Publisher, Universitas Sumatera Utara, 2023)
Background: Patients with HIV-AIDS are at increased risk for both opportunistic infections, such as cerebral toxoplasmosis, and cognitive impairment. IgG anti-Toxoplasmosis gondii (T.gondii) is a marker for latent infection. However, its role in cognition in HIV patients remains unclear. The study aims to determine the correlation between Ig-G anti-T.gondii and each domain cognitive function in HIV patients with cerebral toxoplasmosis. Method: This was a cross-sectional study involving 110 HIV patients with cerebral toxoplasmosis who met the inclusion and exclusion criteria. We assessed cognitive function using Montreal Cognitive Assessment Indonesian Version (MoCA-INA) and measured the IgG anti-T.Gondii using the ELISA method. The Spearman correlation test was used to determine the correlation between Ig-G anti-T.gondii with each cognitive domain. Results: There was a significant correlation between IgG anti-T.gondii and cognitive function. (p = 0.004, r = -0.275). There was also significant relation between IgG anti-T.gondii with attention (p = 0.046, r =-0.19), abstraction (p = 0.036, r = -0.2), and delayed recall (p = 0.047, r =-0.19). But there was no significant relation between Ig-G anti-T.gondii with visuospatial (p = 0.171), naming (p = 0.521), language (p = 0.810), and orientation (p = 0.11) Conclusion: Lower Level Of IgG Anti-Toxoplasmosis Gondii Antibodies Is Associated With Worse Cognitive Function In Human Immunodeficiency Virus-Acquired Immunodeficiency Syndrome (HIV-AIDS) Patients with Cerebral Toxoplasmosis